DECREASED SEX HORMONE-BINDING GLOBULIN (SHBG) SERUM LEVEL IN POLYCYSTIC OVARIAN SYNDROME PATIENTS (PCOS): Penurunan Kadar Sex Hormone-Binding Globulin Serum (SHBG) pada Pasien Polycystic Ovarian Syndrome Patients (PCOS) - Azalia Talitha Zahra; M. Irsan Saleh; Zen Hafy; Yusuf Effendi; Ziske Maritska; Iche Andriyani Liberty (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Classic symptoms of PCOS including irregular menstruation, high serum androgen concentration, hirsutism, and infertility or subfertility. Low serum sex hormon binding globulin (SHBG) may cause increase of free serum androgen which in turn may cause ovarian dysfunction and clinical symptoms associated with hyperandrogenism. This study aims to look the difference of serum SHBG concentration in PCOS patients and healthy control in Palembang, South Sumatra. This was a case-control study involved 36 PCOS patients and 36 healthy controls. Patient serum was collected and SHBG concentration was conducted using ELISA according to manufacturer instruction. Median serum SHBG concentration in PCOS case group was 152.524 nmol/L (min. 5.756 nmol/L, max. 1539.383 nmol/L). meanwhile, median serum SHBG concentration in control group was 971.449 nmol/L (min. 114.479 nmol/L, max. 1944.036 nmol/L). The difference was found to be statistically significant, with p < 0.001 according to Mann-Whitney test. It is to be concluded that serum SHBG concentration is significantly lower in PCOS patient group compared to healthy control. ABSTRAK Gejala khas PCOS berupa berupa haid tidak teratur, kadar androgen serum yang tinggi, hirsutisme, dan infertilitas atau subfertilitas. Kadar sex hormon binding globulin serum yang rendah menyebabkan peningkatan kadar androgen bebas di serum yang dapat menyebabkan disfungsi ovarium dan gejala klinis yang terkait hiperandrogenisme. Penelitian ini bertujuan untuk melihat perbedaan kadar SHBG serum pada pasien PCOS dan kontrol sehat di Palembang, Sumatra Selatan. Penelitian ini menggunakan metode case control dengan sampel 36 pasien PCOS dan 36 kontrol sehat. Serum darah pasien diambil dan kadar SHBG diperiksa menggunakan ELISA sesuai instruksi pembuat. Kadar SHBG median pada kelompok kasus PCOS adalah 152,524 nmol/L (min. 5,756 nmol/L, maks. 1539,383 nmol/L). sementara itu, kadar SHBG median pada kelompok kontrol adalah 971,449 nmol/L (min. 114,479 nmol/L, maks. 1944,036 nmol/L). Perbedaan tersebut bermakna secara statistik dengan p< 0,001 dengan uji Mann-Whitney. Dapat disimpulkan bahwa kadar SHBG serum pada subjek dengan PCOS lebih rendah secara bermakna dibandingkan dengan kelompok kontrol.